Ozone therapy with local cellular immune modulation and disc progenitor cell implant is safe, effective and efficient - Grangeat AM; Crocce EA; Erario MA; Moviglia Brandolino MT; Piccone SL; Lopez MA; Moviglia GA (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2020)
Low Back Pain (LBP) is a major cause of morbidity with significant economic impact through loss of work (15% in the United Kingdom). Additionally, there is the cost of health care and social support for the affected individual and their family. It is estimated that more than half the population (49%-70%) will experience significant LBP during their lives. Point prevalence from 12% to 30% is reported in western countries [1,2].